Determination of tick-pathogen interactions during acquisition and transmission of Borrelia duttonii by Ornithodoros moubata - Ćetković, Ana (Jihočeská univerzita, 2020)
The goal of this thesis was to investigate the interaction between Borrelia duttonii, a causative agent of TBRF in Africa, and its tick vector Ornithodoros moubata in terms of acquisition and transmission dynamics. The infectivity of frozen sera and infected unfed O. moubata ticks was evaluated. The acquisition efficiency of B. duttonii 1120K3 and Ly isolates by O. moubata was determined and compared. The minimum acquisition time was established as well. Moreover, the sensitivity of Borrelia in the presence of different animal sera was analysed.
Determination of tick-pathogen interactions during acquisition and transmission of Borrelia duttonii by Ornithodoros moubata
Keywords: Borrelia duttonii; Old World; Ornithodoros moubata; spirochetes; relapsing fever; acquisition; transmission; infectivity; tick; host; gene; expression; Vtp; Vmp; sera; mice; sensitivity; Borrelia duttonii; Old World; Ornithodoros moubata; spirochetes; relapsing fever; acquisition; transmission; infectivity; tick; gene; Vtp; Vmp; sera; mice